Internet-based technologies to improve cancer care coordination: Current use and attitudes among cancer patients. Issue 4 (March 2015) - Girault, Anne; Ferrua, Marie; Lalloué, Benoît; Sicotte, Claude; Fourcade, Aude; Yatim, Fatima; Hébert, Guillaume; Di Palma, Mario; Minvielle, Etienne
Abstract Background The uses of internet-based technologies (e.g. patient portals, websites and applications) by cancer patients could be strong drive for change in cancer care coordination practices. The goal of this study was to assess the current utilisation of internet-based technologies (IBT) among cancer patients, and their willingness to use them for their health, as well as analyse the influence of socio-demographics on both aspects. Methods A questionnaire-based survey was conducted in June 2013, over seven non-consecutive days within seven outpatient departments of Gustave Roussy, a comprehensive cancer centre (≈160, 000 consultations yearly), located just outside Paris. We computed descriptive statistics and performed correlation analysis to investigate patients' usage and attitudes in correspondence with age, gender, socioeconomic status, social isolation, and place of living. We then conducted multinomial logistic regressions using R. Results The participation level was 85% (n = 1371). The median age was 53.4. 71% used a mobile phone everyday and 93% had access to Internet from home. Age and socioeconomic status were negatively associated with the use of IBT (p < 0.001). Regarding patients' expected benefits, a wide majority valued its use in health care, and especially, the possibility to enhance communication with providers. 84% of patients reported feeling comfortable with the use of such technologies but age and socioeconomic status had a significant influence. Conclusion Most patients used IBTs every day. Overall, patients advocated for an extended use of IBT in oncology. Differences in perceived ease of use corresponding to age and socioeconomic status have to be addressed.